HUBUNGAN FAMILY CENTERED CARE DENGAN STRESS HOSPITALISASI PADA ANAK USIA PRA SEKOLAH DI RSUD AJIBARANG BANYUMAS - Yoga Prasetia,; Tin Utami,; Atun Raudotul Ma’rifah, (Jurnal Cakrawala Ilmiah, 2022)
During the process, children can experience various events in the form of experiences that are very traumatic and full of stress. The group of children who are very vulnerable to the stress of hospitalization is pre-school children. Hospitalization reactions in pre- school age children show non-adaptive reactions which can be in the form of refusing to eat, frequently asking questions, crying and being uncooperative with officers. Another impact of hospitalization stress is that it can cause children to experience short-term and long-term negative effects, generally in the form of lethargy behavior, sleep disturbances. This study aims to determine the relationship between Family Centered Care and the stress of hospitalization for pre-school children at the Ajibarang Hospital, Banyumas. This study uses quantitative research methods with a cross-sectional approach. Respondents in the study were pre-school children who were being treated in the children's room at Kepodang Atas Hospital Ajibarang Banyumas as many as 30 respondents. The sampling technique used non-probability sampling. Data analysis used univariate analysis and bivariate analysis. The results of this study indicate that the majority of Family Centered Care in the Kepodang Atas pediatric care room at Ajibarang Banyumas Hospital is in the sufficient category (50%). The most dominant stress of hospitalization of pre-school age children in Ajibarang Hospital is mild hospital stress (63.3%). There was a relationship between Family Centered Care and the stress of hospitalization at Ajibarang Hospital with a p value of 0.000. This research is recommended for parents who are expected to be able to use and improve all sources that can improve family center care.